ASAS DESENTRALISASI DAN TUGAS PEMBANTUAN DALAM UU NO. 32 TAHUN 2004 TENTANG PEMERINTAHAN DAERAH - Untung Dwi Hananto (Masalah-Masalah Hukum, 2011)
Decentralization of government authority given to the regional center is intended as an effort to promote community empowerment, growth aspirations and creativity, increase participation of local community in local governance. Therefore, understanding of regional autonomy is defined as an autonomous regional authority to regulate and manage the interests of local people own initiative based on community aspirations in accordance legislation. Medebewind is the assignment of government to the regions andlor village from the provincial government to local governments and I or village, to carry out as well as from local governments to the village. Kata kunci: Asas Desentralisasi, Tugas Pembantuan